If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + x = -10 + 7 Combine like terms: -10 + 7 = -3 3 + x = -3 Solving 3 + x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = -3 + -3 Combine like terms: 3 + -3 = 0 0 + x = -3 + -3 x = -3 + -3 Combine like terms: -3 + -3 = -6 x = -6 Simplifying x = -6
| b/19-7b/19=30/19 | | uz+uw=r | | -52.6+(-84.7)= | | (3+2x)x=54 | | -4.32+39.65= | | 11.5+x-7.7=4.7 | | (100—49)/19 | | -4(0.3x+0.6)-1.3=-0.1 | | 28-1+10=x-1 | | ln(40)-2ln(5)=0 | | 9z+29x=8x-13 | | 34-3x=16 | | -19+x-2=11-19+9 | | 4x+7=20(3-2x)+7 | | 17-8+x=8+7-3 | | -23+(-45)= | | 0.2x+9.7=8.4 | | 3(x+5)=6x+8 | | 8(x-8)=24-3x | | 20+5x+4x-11=180 | | 9(2)+3y=4y-9(4) | | (1/2)(6x-8)=(7/5)(x-5)-(1/5) | | 1x+25=-3 | | -6=x+100 | | 2x+x=359 | | 60=-w+176 | | 36-x=267 | | 158=239-u | | 1(15x)+25=-3 | | 245=-u+123 | | 7/2=3/2n-7/2n | | 5-4x=4x-5-4x-2 |